Analisa Pembangunan Aplikasi Pengolahan Data Akademik Berbasis Web - Anisya, Anisya; Febriadi, Bayu; Hidayat, Wahyu (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2018)
Vocational High School (SMK) is one form of a formal education unit that provides vocational education as a continuation of (Junior High School) SMP / MTs and equal. One of them is SMK N 1 Koto Baru. In the processing of academic data using Microsoft Excel and Microsoft Word applications, the number of students approximately 550 students are divided into 9 departments so it takes a long time in the processing of academic data. This study aims to analyze the development of SMK N 1 Koto Baru to process academic data such as attendance, assessment of daily exams, duties, and final exams. The development of this system uses PHP programming language and MySQL database. The results obtained from this study in the form of student report cards per academic year.